The Influence of Job Stress, Compensation, and Work-Life Balance on Turnover Intention (A Case Study on Employees of Nest Group Indonesia) - Syifa Nabilah; Hery Derajad Wijaya (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the effect of Job Stress, Compensation, and Work-Life Balance on Turnover Intention among employees at Nest Group Indonesia. The study involved a population and sample of 72 employee respondents, selected through a sampling method. This thesis employs a causal research design, with data collected using questionnaires distributed via Google Forms. Data analysis was conducted using the Partial Least Squares (PLS) software. The results of the study indicate that job stress has a positive and significant effect on the turnover intention of employees at Nest Group Indonesia. Compensation also has a positive and significant effect on the turnover intention of the company's employees. Furthermore, work-life balance has a positive and significant effect on the turnover intention of employees at Nest Group Indonesia.